2020
DOI: 10.5853/jos.2020.00689
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Led Smartphone Electrographic Monitoring for Atrial Fibrillation after Ischemic Stroke: SPOT-AF

Abstract: Background and Purpose Paroxysmal atrial fibrillation (PAF) underlying acute stroke frequently evades detection by standard practice, considered to be a combination of routine electrocardiogram (ECG) monitoring, and 24-hour Holter recordings. We hypothesized that nurse-led in-hospital intermittent monitoring approach would increase PAF detection rate.Methods We recruited patients hospitalised for stroke/transient ischemic attack, without history of atrial fibrillation (AF), in a prospective multi-centre observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The sample-size calculation is based on the primary endpoint: “the detection probability for each group.” The detection probability was assumed as standard treatment: 2.5%, smartphone recorder: 8.5%, single-lead device: 14.5%, based on the SPOT-AF trial ( 13 ) and a previous assessment of a simulation in the CRYSTAL-AF trial ( 18 ). Non-inferiority margin was assumed to be 2.3% conservatively based on the difference in expected detection rates between single-lead device (14.5%) and smartphone-based device (8.5%) ( 13 , 18 ). First, for determining the single-lead device's superiority to standard strategy at a significance level (alpha) of 5%, power (1-beta) of 80%, and margin of 2.3%, we calculated that 108 participants are needed in each group, assuming a 10% drop-out rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample-size calculation is based on the primary endpoint: “the detection probability for each group.” The detection probability was assumed as standard treatment: 2.5%, smartphone recorder: 8.5%, single-lead device: 14.5%, based on the SPOT-AF trial ( 13 ) and a previous assessment of a simulation in the CRYSTAL-AF trial ( 18 ). Non-inferiority margin was assumed to be 2.3% conservatively based on the difference in expected detection rates between single-lead device (14.5%) and smartphone-based device (8.5%) ( 13 , 18 ). First, for determining the single-lead device's superiority to standard strategy at a significance level (alpha) of 5%, power (1-beta) of 80%, and margin of 2.3%, we calculated that 108 participants are needed in each group, assuming a 10% drop-out rate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies such as the Apple Heart Study ( 10 ), REHEARSE-AF (REmote HEArt Rhythm Sampling using the AliveCor heart monitor to scrEen for Atrial Fibrillation) ( 11 ), and the SCREEN-AF (SCREENing for Atrial Fibrillation) ( 12 ) proved the usefulness of single-lead ECG, their results were based on data from the general population and not data that was specifically obtained from patients with an ischemic stroke or transient ischemic attack (TIA). In 2020, a study of nurse-led monitoring during stroke (SPOT-AF) demonstrated the feasibility and efficacy of a single-lead ECG recorder for post-stroke AF detection ( 13 ). A prospective study for comparing the event recorder (2 times daily) with a 7-day Holter monitor is ongoing ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…supporting the use of handheld ECG devices in the stroke unit to screen for AF poststroke, 106,107 which may be of particular relevance to the Asia Pacific region and could be used in places without telemetry.…”
Section: Screening Tools For Detection Of Af Poststrokementioning
confidence: 99%
“…The timing of monitoring is crucial, as identification that AF was the likely cause of stroke will change treatment from antiplatelets to oral anticoagulants. Early monitoring in the stroke unit is not always possible, but when nurses do monitor for AF systematically, a higher rate of AF detection than usual care is observed [3] . Unfortunately, even in high income countries where telemetry is available, ECG monitoring is not always performed, often due to patients being absent for multiple investigations including imaging.…”
mentioning
confidence: 99%
“…If telemetry is performed, stroke unit nurses and even medical staff may not be experienced in arrhythmia diagnosis. Furthermore, although standard practice is a 24-hour Holter performed after discharge, only ~25% of patients receive this [3] , [4] . Thus, many cases of paroxysmal AF go unrecognised in this crucial early post-stroke period.…”
mentioning
confidence: 99%